HUMAN BEHAVIORAL COROLLARY ON INDUSTRIAL WORKPLACE - Fazil, I.; Kirmani, Z. U.; Hanif, M.; Saeed, A.; Khurshid, A. (The Nucleus, 2020)
This paper highlights a number of initiatives taken for the introduction of behavior-based safety concepts and customized process control solutions to encourage and instill safe behavior in employees at Attock Refinery Limited (ARL), Morgah Rawalpindi, Pakistan. A Safety culture is entirely dependent on the attitude of employees towards safety. After all, those who actually perform the work are responsible for their safety as well as that of those around them, and also for any accident that occurs whilst they work. In 2005, ARL established a Health Safety Environment (HSE) Department reporting directly to the CEO and it now stands transformed into the HSEQ Department with Quality having been added to its portfolio, with the logic that it is the Quality of our systems and processes that also determines the possibility or otherwise of safe/unsafe behavior. The need was felt to measure, analyze and then control unsafe behavior at the workplace. In spite of providing safety systems and necessary hardware, incident data shows that the majority of misfortunes are triggered by employees’ unsafe attitude, proclivity to take shortcuts and intuitive-based decisions, bypassing Standard Operating Procedures (SOPs). Human behavior is a very complex subject as it is linked not only to the workplace environment but has origins from home and upbringing as well. An attempt was, nevertheless, necessary to develop a tool of customized behavioral assessment tool in order to gauge the employees’ behavior. On a scale of 1-100, marks were allocated to areas including safety attitude within the department(s), working conditions, supervisor’s behavior towards worker safety, job loyalty, personal attitude towards job safety, seriousness towards safety, training and the employees’ view about the HSEQ department. This study, based on one-on-one interviews with employees, yielded what we will term employees’ potential towards unsafe behaviors, which would facilitate subsequent planning and customized training to overcome weak behavioral aspects of personality.